1985
DOI: 10.1007/bf02310016
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated drug resistance of shigellae in Kuwait

Abstract: Of 153 clinical isolates of shigellae examined, 64.7% belonged to Shigella flexneri, 18.9% to Sh. sonnei, 11.8% to Sh. boydii and 4.6% to Sh. dysenteriae. Part of these isolates were resistant to sulfamethoxazole and streptomycin (88.2% each), ampicillin (66.7%), tetracycline (63.4%) and co-trimoxazole (43.1%), with levels of resistance (MIC50 and MIC90) being invariably high. Resistance to three or more drugs (multidrug resistance) was seen in 77.8% of the isolates. All the 25 strains examined for transfer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…to antibacterial drugs has been reported from different parts of the world and is increasing [5]. First observed in S. flexneri in Japan [6], the development of transferable multi-drug resistance was soon reported elsewhere, including Taiwan [4], and was also observed in other shigellae [7]. In spite of the prevalence of shigellosis in Taiwan, there have been few epidemiological studies, and resistance patterns in this area have not as yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…to antibacterial drugs has been reported from different parts of the world and is increasing [5]. First observed in S. flexneri in Japan [6], the development of transferable multi-drug resistance was soon reported elsewhere, including Taiwan [4], and was also observed in other shigellae [7]. In spite of the prevalence of shigellosis in Taiwan, there have been few epidemiological studies, and resistance patterns in this area have not as yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in resistance were seen in the case of erythromycin, chloramphenicol, streptomycin and tetracycline. 1286 salmonellae are known to ferment lactose, in this aspect Chugh., (1978) suggested that this characteristic found in these Salmonella is attributed to Lac + plasmid either as a separate entity or in conjunction with drug resistance. Chander et al (1980) suggested that certain Salmonella serotypes viz.…”
mentioning
confidence: 99%